Save Your Maximum Tolerated Dose: How to Diagnose Procedure-Related Spinal Cord Lesions After Lumbar Intrathecal Bolus Administration of Oligonucleotides in Cynomolgus Monkeys. (November 2020) - Korte, Sven; Luft, Jorge; von Keutz, Anne; Runge, Frank; Mecklenburg, Lars; Wozniak, Magdalena Maria; Zander, Serge; Ludwig, Florian Timo; Pajaziti, Betina; Romeike, Annette; Korytko, Peter
Many potential drugs for treatment of neurodegenerative diseases, particularly antisense oligonucleotides (ASOs), are administered via lumbar intrathecal injection, because these drugs do not cross the blood–brain barrier. Intrathecal injection is a well-established method in cynomolgus monkeys, a species that is used in preclinical safety assessment when other nonrodent species cannot be used. The authors completed intrathecal ASO administration in over 30 preclinical safety studies (>1000 animals and >4500 dose administrations) during which we observed 3 cases of procedure-related spinal cord necrosis (incidence <0.1%). We describe clinical symptoms, diagnostic approaches, morphological features, and prognosis of this rare injury, and compare these findings with typical drug-related findings of ASOs dosed by intrathecal injection. The low incidence of procedure-related and dose-limiting lesions confines this analysis to a small sample set. The pattern of effects is similar across all monkeys despite differences in age, body weight, and intrathecal injection site. All 3 cases presented a combination of the following findings: blood in cerebrospinal fluid at time of injection, clinical signs that increase in severity within a day of dosing, lameness of both hind limbs, reduced muscle tone, and loss of patellar, foot grip, and/or anal reflexes. In all cases, magnetic resonance imaging (MRI) showed a linear hyperintense lesion in the lumbar spinal cord. In 2 cases, this hyperintensity was associated with evidence of spinal cord edema. We conclude that a pattern of in-life and pathology findings, including noninvasive MRI assessment, is indicative of procedure-related effects.